Peran Pendidik Terhadap Peserta Didik UntukMenanamkan Budaya Sopan Santun DalamPembelajaran Pendidikan Kewarganegaraan - Suci Permata Rahmadhani; lutfi Ardiansyah; Nela Rofisian (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
Education is a conscious effort to prepare students through guidance, teaching and/or training activities for their role in the future so that they have the self-control, personality, intelligence and skills needed by themselves and society. In thinking about education, it is first necessary to know two terms which are almost the same in form and are often used in the world of education, namely pedagogy and pedagogy. This research uses a qualitative method with a library research approach using literature studies regarding texts contained in the book Al-Akhlak Li Al Banin Volumes 1-2 written by Syaikh Umar Baraja. Because what is being studied is written text in the form of a corpus (data used as a source of research material), this research is classified as a library research approach. Library research (library research) is research carried out using literature (libraries) in the form of books, notes or reports of research results from previous research.